Correlates of unintended pregnancy among currently pregnant married women in Nepal - Soonthorndhada Kusol; Adhikari Ramesh; Prasartkul Pramote (BMC, 2009)
Abstract Background Women living in every country, irrespective of its development status, have been facing the problem of unintended pregnancy. Unintended pregnancy is an important public health issue in both developing and developed countries because of its negative association with the social and health outcomes for both mothers and children. This study aims to determine the prevalence and the factors influencing unintended pregnancy among currently pregnant married women in Nepal. Methods This paper reports on data drawn from Nepal Demographic and Health Survey (NDHS) which is a nationally representative survey. The analysis is restricted to currently pregnant married women at the time of survey. Association between unintended pregnancy and the explanatory variables was assessed in bivariate analysis using Chi-square tests. Logistic regression was used to assess the net effect of several independent variables on unintended pregnancy. Results More than two-fifth of the currently pregnant women (41%) reported that their current pregnancy was unintended. The results indicate that age of women, age at first marriage, ideal number of children, religion, exposure to radio and knowledge of family planning methods were key predictors of unintended pregnancy. Experience of unintended pregnancy augments with women's age (odds ratio, 1.11). Similarly, increase in the women's age at first marriage reduces the likelihood of unintended pregnancy (odds ratio, 0.93). Those who were exposed to the radio were less likely (odds ratio, 0.63) to have unintended pregnancy compared to those who were not. Furthermore, those women who had higher level of knowledge about family planning methods were less likely to experience unintended pregnancy (odds ratio, 0.60) compared to those having lower level of knowledge. Conclusion One of the important factors contributing to high level of maternal and infant mortality is unintended pregnancy. Programs should aim to reduce unintended pregnancy by focusing on all these identified factors so that infant and maternal mortality and morbidity as well as the need for abortion are decreased and the overall well-being of the family is maintained and enhanced.